E-BUSINESS APLICATION TO IMPROVE TRACEABILITY AND SUPPLY CHAIN FOR FRESH FOOD - Ruxandra-Eugenia POP; Alexandra BRĂTULESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The agri-food sector in Romania is of particular importance for the market economy, referring to agriculture, food industry, commerce, and not ultimately the final consumer. Due to changes in consumer behavior of agri-food products, it is increasingly desirable to know the food traceability, the concept from farm to fork being constantly developing. In the context of ensuring food security, it is important to have an efficient monitoring of the food route in order to keep it fresh. An important factor in this process is the new communication and information technologies, which are in continuous development especially from the applicative point of view. This paper aims to support the producers and suppliers of fresh agri-food products in order to improve management at the short supply chain by exemplifying some types of computer tools that can be used in their work. The conclusion was that GIS maps and GPS location enable the use to know where production is located and the storage conditions.